PELAYANAN PUBLIK DALAM PENGURUSAN E-KTP OLEH UPT DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL DI KECAMATAN KUBU BABUSSALAM KABUPATEN ROKAN HILIR TAHUN 2019 - ", Ismawati; ", Wazni (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
E-KTP making service is one form of public service provided by the government. e-KTP as the official identity of the population which is regulated by the implementing agency which is valid throughout the region. Since the division of Kubu Babussalam sub-district in 2012 the e-KTP service has experienced various problems. So this study aims to analyze the public services in the management of e-KTP at the UPT Department of Population and Civil Registration in Kubu Babussalam sub-district and the obstacles in the implementation of these services. This research is a field research using descriptive research and a qualitative approach. The research location is at the UPT Department of Population and Civil Registration in Kubu Babussalam Subdistrict, Rokan Hilir Regency. This study uses the theory of responsiveness, responsiveness, and accountability in achieving research objectives. Then the data collection techniques use interviews, observation and documentation. While the data analysis used qualitative descriptive data analysis techniques.The results of the study indicate that public services in managing e-KTP by the UPT Department of Population and Civil Registration in Kubu Babussalam District can be seen from three aspects, namely. (1) Responsiveness, by providing e-KTP services according to community needs, arranging service agendas and priorities and developing programs according to community needs and aspirations. (2) Responsibility, by conducting programs in order to fulfill demand figures and provide good service to the community. (3) Accountability, namely by following procedures or service procedures that are easy to understand by the public, and are not complicated. Then regarding the obstacles in service found such as recording machines, operator and network disturbances, queuing services, ignorant community members and the lack of signs in the service notification.Â Keywords: Public Service, e-KTP, UPT Department of Population and Civil Registry.Â